2023
DOI: 10.1007/s10916-023-01934-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Versus Periodic Vital Sign Monitoring on Disease Severity of Patients with an Unplanned ICU Transfer

Abstract: Continuous vital sign monitoring (CM) may detect ward patient’s deterioration earlier than periodic monitoring. This could result in timely ICU transfers or in a transfer delay due to misperceived higher level of care on the ward. The primary objective of this study was to compare patient’s disease severity upon unplanned ICU transfer, before and after CM implementation. We included a one-year period before and after CM implementation between August 1, 2017 – July 31, 2019. Before implementation, surgical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Early detection of deterioration in hospitalized patients by wearable sensors caused a reduction in intensive care unit admissions, rapid response teams, cardiac arrest calls, and complications [ 28 , 29 ]. However, a recent study found that disease severity, length of stay, and mortality of patients with unplanned intensive care unit admission was not affected by continuous vital sign monitoring on the ward [ 30 ]. In addition to early deterioration outcomes, other reported outcomes, as a result of continuous monitoring, were better pain relief and higher patient satisfaction [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early detection of deterioration in hospitalized patients by wearable sensors caused a reduction in intensive care unit admissions, rapid response teams, cardiac arrest calls, and complications [ 28 , 29 ]. However, a recent study found that disease severity, length of stay, and mortality of patients with unplanned intensive care unit admission was not affected by continuous vital sign monitoring on the ward [ 30 ]. In addition to early deterioration outcomes, other reported outcomes, as a result of continuous monitoring, were better pain relief and higher patient satisfaction [ 31 ].…”
Section: Resultsmentioning
confidence: 99%